Analysis of flexural capacity of a novel straight-side U-shaped steel-encased concrete composite beam. (1st September 2021) - Yan, Qiwu; Zhang, Zheng; Yan, Jin; Laflamme, Simon
Highlights: Proposes a new straight-side U-shaped steel-encased concrete composite beam (SUSCCB). The capacity and initial stiffness of proposed beam are higher compared against traditional U-shaped steel-encased concrete composite beam. A finite element model (FEM) is developed to conduct a parametric study of the SUSCCB. Analytical flexural capacity of the SUSCCB is derived based on the simplified plastic theory. Abstract: This paper proposes a novel straight-side U-shaped steel-encased concrete composite beam (SUSCCB). The SUSCCB is constituted by encasing the top sections of the U-shaped steel plates directly into the concrete flange, with the composite action generated through perfobond connections consisting of reinforcement bars transversely passing through perforations in the encased top sections of the steel plates. It is engineered to overcome the shortcomings of the existing varus or valgus U-shaped steel-encased concrete composite beams (USCCB), for which the installation of shear connectors can be complex and costly to achieve because of the numerous required welds. The main objective of this paper is to study the flexural behavior of the proposed SUSCCB and develop a method for calculating its flexural capacity. A finite element model (FEM) is developed and validated against available USCCB experimental results. After, the validated FEM is used to conduct a parametric study of the SUSCCB. The flexural behavior is assessed from the strain distribution, stress analysis, and load–deflection curves. Results show that the flexural performance of the SUSCCB is superior to that of a traditional USCCB, and that its flexural capacity can be calculated through the simplified plastic theory. Lastly, the analytical flexural capacity of the SUSCCB is derived. The analytical values show close agreement with results from the numerical simulations.